Nigerian Journalist's Strategies for Overcoming Language Barriers in International News Reporting: A Study of Channels Television - Oluwafisayo Ogunyemi; Fadeyi Oluwadamilola Dorcas (LingLit Journal Scientific Journal for Linguistics and Literature, 2026)
Language is critical in producing and disseminating international news, as journalists must gather and interpret information across linguistic and cultural boundaries. This qualitative study, anchored in Gatekeeping and Framing Theory, used in-depth interviews with five Channels Television editorial staff to examine how Nigerian journalists handle language barriers in international reporting. Findings show barriers include interpreting foreign-language documents, understanding culturally embedded expressions, verifying non-English sources, and communicating with foreign-language interviewees. Journalist’s counter these with machine translation tools, multilingual professional networks, international wire services, editorial review, and AI-assisted verification platforms. Though these strategies improve accuracy and efficiency, they’re limited by deadlines, funding, inadequate language training, and dependence on external intermediaries. The study concludes language barriers still reduce the quality and depth of international reporting in Nigerian newsrooms, and recommends investment in language training, multilingual verification systems, and cross-cultural communication skills to boost credibility.